Novelty seeking and medication adherence in patients with schizophrenia - Aukst-Margetić, Branka (Array, 2011)
The study explored the association between temperament and character and medication adherence in 76 patients with schizophrenia. Patients were assessed with the Temperament and Character Inventory, the Beck Depression Inventory, and the Positive and Negative Syndrome Scale. First-degree relatives were used as informants on adherence. The patients differed in their adherence based on the effect of gender, as males were found to be less adherent than females. Adherence differed based on novelty seeking. The temperament of the patient should be considered during the assessment of adherence.